Specific visualization of live type A spermatogonia of Pacific bluefin tuna using fluorescent dye-conjugated antibodies†. Issue 6 (1st April 2019) - Ichida, Kensuke; Kawamura, Wataru; Miwa, Misako; Iwasaki, Yoshiko; Kubokawa, Tsubasa; Hayashi, Makoto; Yazawa, Ryosuke; Yoshizaki, Goro
Abstract: During our previous work toward establishing surrogate broodstock that can produce donor-derived gametes by germ cell transplantation, we found that only type A spermatogonia (ASGs) have the potency to colonize recipient gonads. Therefore, the ability to visualize ASGs specifically would allow the sequential analysis of donor cell behavior in the recipient gonads. Here we produced monoclonal antibodies that could recognize the cell surface antigens of ASGs in Pacific bluefin tuna ( Thunnus orientalis ), with the aim of visualizing live ASGs. We generated monoclonal antibodies by inoculating Pacific bluefin tuna testicular cells containing ASGs into mice and then screened them using cell-based enzyme-linked immunosorbent assay (ELISA), immunocytochemistry, flow cytometry (FCM), and immunohistochemistry, which resulted in the selection of two antibodies (Nos. 152 and 180) from a pool of 1152 antibodies. We directly labeled these antibodies with fluorescent dye, which allowed ASG-like cells to be visualized in a one-step procedure using immunocytochemistry. Molecular marker analyses against the FCM-sorted fluorescent cells confirmed that ASGs were highly enriched in the antibody-positive fraction. To evaluate the migratory capability of the ASGs, we transplanted visualized cells into the peritoneal cavity of nibe croaker ( Nibea mitsukurii ) larvae. This resulted in incorporated fluorescent cells labeled with antibody No. 152 being detected in the recipient gonads, suggesting that the visualized ASGs possessed migratory and incorporation capabilities. Thus, the donor germ cell visualization method that was developed in this study will facilitate and simplify Pacific bluefin tuna germ cell transplantation. Abstract : We established a technique for visualizing and tracing live type A spermatogonia (ASGs) of Pacific bluefin tuna using fluorescent dye-conjugated monoclonal antibodies that can recognize the cell surface antigens of ASGs.